La vega, colombia: healthy municipality. a case study (2002)
In 1992 Colombia adopted the strategy of healthy municipalities, renamed in 1997 as healthy municipalities for peace. This strategy was promoted from different sectors and directed to social mobilization aimed at locally achieving equity, quality of life, and social development, thus allowing the creation of favorable-for-peace environments. Some municipalities have applied this strategy and both its processes as well as its results must be studied in order to learn from this experience. One of these municipalities was La Vega in the department of Cundinamarca. A case study of this municipality was carried out in order to evaluate some of the components of this strategy such as political involvement, healthy public policies, articulation between sectors and the organizational structure supporting this strategy. In this municipality the process began in 1990 as a primary health care strategy. In 1992 the mayor declared his commitment to this strategy and a plan of participative development, aimed at improving the quality of life of its population, was implemented. In this same year the Colombian Ministry of Health and the Pan American Health Organization recognized it as a healthy municipality and in 1997 it obtained the national healthy municipality prize. The relevant aspect of La Vega has been the process of community participation, basis of the work aimed at improving peoples´ health.